Isolation of the B Cell Immune Synapse for Proteomic Analysis - Cunha Diogo M; Hernández-Pérez Sara; Mattila Pieta K (Humana Press, 2025)
Recent technical developments have fueled increasing utilization of proteomics to gain new insights into various aspects of cellular behavior. In this chapter, we describe a method to specifically isolate immune synapses from mouse primary B cells. The method utilizes antibody-coated magnetic beads to induce the formation of the immune synapses and describes a protocol for the extraction of the cell-bead adhesions for mass spectrometry analysis. Finally, this method enables unveiling the large-scale protein content of the immune synapse.
The Immune Synapse